Nieliniowe Zagadnienia Deformacji Sprężysto-Plastycznych i Pełzania Membran Kołowych - Bychawski, Z.; Kopecki, H. (Engineering Transactions, 1967)
The authors formulate the problem of combined nonlinear deformation of a plane circular membrane showing instantaneous elastic-plastic strain and creep. The fundamental set of two nonlinear differential equations for the stress function and the deffection function is solved by the method of double power series involving a small physical quantity. The efficacy of this method is illustrated by an example.